2006
DOI: 10.1373/clinchem.2005.0525144
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Improving Serum Creatinine Measurement: A Report from the Laboratory Working Group of the National Kidney Disease Education Program

Abstract: Background: Reliable serum creatinine measurements in glomerular filtration rate (GFR) estimation are critical to ongoing global public health efforts to increase the diagnosis and treatment of chronic kidney disease (CKD). We present an overview of the commonly used methods for the determination of serum creatinine, method limitations, and method performance in conjunction with the development of analytical performance criteria. Available resources for standardization of serum creatinine measurement are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
481
1
23

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,058 publications
(523 citation statements)
references
References 116 publications
6
481
1
23
Order By: Relevance
“…The strengths of this study are: its large sample size, which allowed a robust estimate of between‐group differences in efficacy; the requirement for duplicate eGFR measurements during screening that ensured a population with stable renal status; and uptitration of dapagliflozin to its maximal approved dose (achieved in approximately 95% of patients). Lastly, the CKD‐epi formula used to estimate GFR in this study is considered more accurate and less likely to underestimate GFR at higher levels of renal function (≥ 60 mL/min/1.73 m 2 ) than the Modification of Diet in Renal Disease estimate 24, 25…”
Section: Discussionmentioning
confidence: 94%
“…The strengths of this study are: its large sample size, which allowed a robust estimate of between‐group differences in efficacy; the requirement for duplicate eGFR measurements during screening that ensured a population with stable renal status; and uptitration of dapagliflozin to its maximal approved dose (achieved in approximately 95% of patients). Lastly, the CKD‐epi formula used to estimate GFR in this study is considered more accurate and less likely to underestimate GFR at higher levels of renal function (≥ 60 mL/min/1.73 m 2 ) than the Modification of Diet in Renal Disease estimate 24, 25…”
Section: Discussionmentioning
confidence: 94%
“…It is recommended that laboratories report GFR as 460 ml min À1 instead of the actual value. 19 In this study, we reported the actual values obtained by MDRD and CKD-EPI to evaluate the study outcome. In addition, the abbreviated form of MDRD was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When it occurs, ARF is associated with a significant increase in risk for complications and death [3,4,5,6], as well as increased length of hospital stay and costs [3, 4]. Yet, despite the importance of ARF in decompensated CHF, there has been limited published data regarding this complication.…”
Section: Introductionmentioning
confidence: 99%